2015
DOI: 10.1186/s12935-015-0232-y
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral potency of methanolic extract from Nitraria retusa leaves via its immunomodulatory effect

Abstract: BackgroundThe purpose of this study was to assess the antitumoral effect of the methanol extract (MeOH) from Nitraria retusa leaves and to investigate its immunomodulatory activity that mediated the prevention of tumor progression in tumor-bearing mice.MethodsBalb/c mice weighing 18–20 g were subcutaneously implanted with B16-F10 cells then injected intra-peritoneally, 7 days later with (200 mg/kg bw) of MeOH extract, for 21 days. After euthanization on day 21, the tumors were weighed. Lymphocyte proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…They suggested that the protective action of N. retusa fruit extract could result from its content of the phenolic compounds. Boubaker et al (2018) indicated that treatment of tumor-induced mice with leaf extracts of N. retusa showed anti-tumor activity which was attributed to its most important components in the N. retusa, namely, palmitic acid and β-sitosterols (Boubaker, Chaabane, et al, 2015a;Boubaker, Mokdad Bzeouich, et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the protective action of N. retusa fruit extract could result from its content of the phenolic compounds. Boubaker et al (2018) indicated that treatment of tumor-induced mice with leaf extracts of N. retusa showed anti-tumor activity which was attributed to its most important components in the N. retusa, namely, palmitic acid and β-sitosterols (Boubaker, Chaabane, et al, 2015a;Boubaker, Mokdad Bzeouich, et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The successive methanol extract of Ficus benghalensis has been known to have immunostimulant activity in lymphocyte proliferation such as T cells and B cells (26). Another in vivo experiment in tumor-bearing mice proved the methanol extract of Nitraria retusa leaves significantly promoted splenocyte proliferation and boosted the activity of natural killer cells and cytotoxic T lymphocytes (27). Similarly, in vitro and in vivo experiments revealed that Mesembryanthemum crystallinum extract was able to enhance human B and T cell lines proliferation (28).…”
Section: Discussionmentioning
confidence: 99%